Mental wellbeing and quality of life in prostate cancer (MIND-P): Protocol for a multi-institutional prospective cohort study - Oliver Brunckhorst; Jaroslaw Liszka; Callum James; Jack B. Fanshawe; Mohamed Hammadeh; Robert Thomas; Shahid Khan; Matin Sheriff; Hashim U. Ahmed; Mieke Van Hemelrijck; Gordon Muir; Robert Stewart; et al. (PLoS ONE, 2023)
Background The mental wellbeing implications of a prostate cancer diagnosis are increasingly being realised. Significant mental health symptoms such as depression and anxiety, along with related constructs such as fear of cancer recurrence, body image and masculine self-esteem issues are prevalent. However, less is understood about potential prognostic factors for these outcomes in prostate cancer patients. Therefore, this study aims to primarily explore potential treatment, patient and oncological factors associated with mental wellbeing outcomes in the initial prostate cancer follow-up period. Methods MIND-P is a multi-institutional prospective cohort study recruiting newly diagnosed prostate cancer patients for 12-month follow up. It will aim to recruit a final sample of 300 participants undergoing one of four treatment options: active surveillance, radical prostatectomy, radical radiotherapy, or hormone monotherapy. Questionnaire-based data collection consists of multiple validated mental, physical, and social wellbeing outcomes at baseline and 3-monthly intervals until study completion. Primary analysis will include evaluation of treatment undergone against multiple mental wellbeing outcomes. Secondary analysis will additionally explore multiple patient and oncological prognostic factors of potential importance, along with the cumulative incidence of these outcomes, symptom trajectory and their association with subsequent functional and social outcomes. Conclusion This cohort study aims to add to the existing limited literature evaluating significant prognostic factors for multiple mental wellbeing outcomes in newly diagnosed prostate cancer patients. This may be of potential use for guiding future prognosis research and of clinical use for identifying individuals potentially requiring additional surveillance or support during routine cancer follow up. Study registration This study was prospectively registered on ClinicalTrials.gov (NCT04647474).